BS ISO 6363-3. Wrought aluminium and aluminium alloys. Cold-drawn rods/bars, tubes and wires. Part 3. Drawn round bars and wires. Tolerances on form and dimensions (symmetric plus and minus tolerances on diameter) (9th June 2021) - British Standards Institution,
No abstract available